Diseño de indumentaria a partir del estudio del bordado de la vestimenta femenina de la comunidad Pilahuín - Tisalema Sisa, María Selena (2024)
The design of casual clothing based on the study of the embroidery of the female clothing of the Pilahuín community seeks to integrate cultural elements in fashion. Pilahuín, an indigenous community, is known for its detailed embroidery, which is an expression of identity and cultural heritage. These embroideries, characterized by their intricate designs and colors, represent symbols and motifs that reflect the worldview, history and daily life of the community. The process of adapting these traditional embroideries to casual clothing involves an in depth study of the shapes, figures and meanings behind each design. This study allows to identify which elements can be harmoniously integrated into the garments, without losing the cultural essence, balancing authenticity with functionality, ensuring that the garments are comfortable and suitable for everyday use. In addition, the visualization of the stylized shapes and figures of the embroidery of the Pilahuín community's female clothing in the casual clothing line establishes a connection with the indigenous community; the casual clothing line is a means of expressing cultural and social identities. The analysis carried out during the project has offered valuable insight into the use of clothing as a tool to disseminate knowledge, heritage, history and the community's heritage. That said, the design process incorporated stylized shapes and forms of embroidery into the casual online apparel collection, the apparel collection seeks to disseminate the indigenous community and encourage the integration of cultural elements into everyday casual wear.